The miracles of Muhammad (pbuh) [videorecording] - Sheikh Yusuf Estes; One Islam Production; ICRA Youth Centre, Inc.; Saba Islamic Media ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
The spaker, Sheikh Yusuf Estes talk on the miracles of Muhammad (pbuh). This talk answered all the questions regarding the miracles of Muhammad (pbuh) as what its states in Al-Quran
Title from title screen
Speaker: Sheikh Yusuf Estes
Keywords: Miracles (Islam); Muhammad, -- Prophet, -- d. 632 -- Miracles